Social Sanctions and Deterrent Effects for Money Politics Criminals in Elections - Hadi, Dejan Abdul; Ambarwati, Tri Sandi; Fadhlika, Zulfa Ã¢â‚¬ËœAzzah (Law Research Review Quarterly, 2018)
Election is a means of implementing popular sovereignty carried out in a direct, general, free, confidential, honest and fair manner by guaranteeing and legitimating the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Candidates who will be able to prosper and make people happy, But we know that this people's hope is not damned by the election process which is often not criminal the calen pair and the sukic team One of the acts is violated by the criminal action of the candidate pairs and the team. To minimize the practice of moneypolitic, our team has a solution by means of a partner, a candidate who has done money polyic so that he can do it in publik and be subject to a double fine as a substitute for the amount of money that has been used to bribe the people to the state. criminal Later this money can be used for the interests of the people. However, if the recapitulation, the candidate who has been found out and not willing to admit and replace, the money is recorded as the case, then the Commission will report to the nezen court. This will get more money and the state. With the existence of this regulation, the candidates will fight twice if they want to explore Money Politic s. To the Ethics Council, the alleged bribery will lead to elections, Money Politic s, fines, public recognition.